2007
DOI: 10.1016/j.exer.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The ocular albinism type 1 gene product, OA1, spans intracellular membranes 7 times

Abstract: OA1 (GPR143) is a pigment cell-specific intracellular glycoprotein consisting of 404 amino acid residues that is mutated in patients with Ocular Albinism Type 1, the most common form of ocular albinism. While its cellular localization is suggested to be endolysosomal and melanosomal, the physiological function of OA1 is currently unclear. Recent reports predicted that OA1 functions as a G protein coupled receptor (GPCR) based on its weak amino acid sequence similarity to known GPCRs, and on demonstration of GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Thus, we established a cell system to study direct GPR143 and tyrosinase interactions. Since previous studies showed that GPR143 is a 7-transmembrane protein (Sone and Orlow, 2007) and tyrosinase is a single membrane-spanning enzyme, both with lumen facing c-termini, we tagged the C-termini of both generating GPR143-EYFP and TYR-ECFP fusion proteins. Thus the fluorescent proteins are located on the same side of the membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we established a cell system to study direct GPR143 and tyrosinase interactions. Since previous studies showed that GPR143 is a 7-transmembrane protein (Sone and Orlow, 2007) and tyrosinase is a single membrane-spanning enzyme, both with lumen facing c-termini, we tagged the C-termini of both generating GPR143-EYFP and TYR-ECFP fusion proteins. Thus the fluorescent proteins are located on the same side of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…GPR143 mutations which affect function may compromise downstream signaling, permitting continuous import of melanosomal proteins into melanosomes and sustained melanogenesis resulting in giant organelles. Based on its topological orientation (Schiaffino et al, 1999; Sone and Orlow, 2007), GPR143 ligands should bind in the organelle lumen and transduce information to the cytosol through heterotrimeric-G protein activation. In this way, GPR143 could function as a “sensor” of melanosomal maturation and prevent formation of macro-organelles (Schiaffino and Tacchetti, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, proteomic analysis of a purified early melanosome fraction obtained from MNT1 cells identified OA1 as a constituent of these organelles (Basrur et al, 2003). Based on sequence homologies and on experimental evidences (Schiaffino and Tacchetti, 2005; Sone and Orlow, 2007), the topological orientation of OA1 on the organelle membrane appears equivalent to canonical seven transmembrane receptors, with the N-terminus toward the lumen and with the C-terminus toward the cytoplasm, and therefore, by comparison with receptors at the plasma membrane, a putative ligand should bind OA1 on the lumenal side of the organelles.…”
Section: Oa1 and Albinismmentioning
confidence: 99%
“…The oa1 mutation leads to giant melanosomes in retinal pigmental epithelium in turn to bring the ocular albinism. OA1 belongs to G-protein-coupled receptor (GPCR) family (Sone and Orlow, 2007). DOPA stimulation on OA1 increases the intracellular calcium concentration via Gq-activation (Lopez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%